EFFECTIVE TECHNIQUES OF IMPROVING STUDENTS' READING COMPREHENSION - Diyarova Aziza Akparjonovna (Web of Journals Publishing, 2024)
Improving students’ reading comprehension is essential for academic success and lifelong learning. This article explores theoretical framework and a range of effective techniques aimed at enhancing students’ ability to understand, analyze, and retain written information. The review focuses on cognitive strategies, such as summarization, self-questioning, and visualization, which help students actively engage with texts and organize their thoughts. Metacognitive strategies like self-monitoring and prediction also play a critical role in fostering deeper comprehension. Collaborative techniques, including reciprocal teaching and peer discussions, promote social interaction and cognitive processing, leading to improved understanding.
Keywords: Reading comprehension, cognitive strategies, metacognitive strategies, summarization, self-questioning, visualization, collaborative techniques, peer discussions, digital tools, educational apps, active reading, engagement, critical thinking, comprehension monitoring, text analysis, reading fluency, interactive learning, student-centered approaches.